2014
DOI: 10.1097/sla.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Alpps

Abstract: ALPPS in mice induces an unprecedented degree of liver regeneration, comparable with humans. Circulating factors in combination with PVL seem to mediate enhanced liver regeneration, associated with ALPPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(72 citation statements)
references
References 29 publications
7
64
0
1
Order By: Relevance
“…This transection selection may not be critical, as the inflammatory response invoked by parenchymal transection14 20 is generally considered to be systemic rather than liver‐specific19 21.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This transection selection may not be critical, as the inflammatory response invoked by parenchymal transection14 20 is generally considered to be systemic rather than liver‐specific19 21.…”
Section: Discussionmentioning
confidence: 99%
“…Both protocols with the same size of FLR should theoretically lead to the same level of portal hypertension. This could indicate that the ALPPS procedure incorporating parenchymal transection and local resection triggers the release of cytokines and growth factors14 21, affecting liver parenchymal integrity and function24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To prove the efficiency of ALPPS in terms of hypertrophy, several experimental studies of ALPPS using an animal model were reported [76-79]. These studies showed that liver regeneration in the ALPPS group was significantly better than the control group (portal vein ligation group).…”
Section: Verification Of the Characteristics Of Alppsmentioning
confidence: 99%